A Longitudinal Analysis of Volunteerism Activities for Individuals Educated in Public and Private Schools. Issue 7 (October 2020) - Cheng, Albert; Sikkink, David
Previous studies offer evidence that U.S. public and private high schools differentially influence volunteerism in adolescence. However, these studies are typically cross-sectional and only consider whether the individual volunteered or not. We address patterns of volunteering from adolescence into adulthood and the kind of volunteering activity in which individuals engage. We also theorize that distinctive civic values within public and private schools together with their respective organizational ties to other civic organizations channel students into particular volunteering activities. Relying on a longitudinal, nationally representative sample of U.S. adolescents, we track volunteering from adolescence into young adulthood and identify the types of volunteering activities in which respondents engage. Results demonstrate that the likelihood of volunteering changes through the life course, and students from different schooling backgrounds systematically sort into specific volunteering activities as our theories predict.